Effective management of polytrauma: Applying the Airway, Breathing, Circulation, Disability, Exposure (ABCDE) method and the Advanced Trauma Life Support (ATLS) protocol to reduce mortality (Research, Society and Development, 2025)
Trauma can be defined as an injury caused by external and violent action. Polytrauma is classified as two or more serious injuries in two or more areas of the body. Knowledge of polytrauma management techniques is essential for managing the condition quickly and accurately, reducing the risk of death. The article aims to review the management of polytrauma patients, seeking to contribute to improving the care of these patients. The narrative literature review methodology was used to prepare the work. The trauma victim patient should be evaluated based on the ATLS protocol, performing an assessment of the airway and stabilization of the cervical spine, ventilation and respiration, circulation, neurological assessment, and exposure and control of the environment, forming the ABCDE. It is essential that health professionals master the ATLS protocol, seeking to provide accurate and agile care to patients.